Self-reported reproductive health of athletic and recreationally active males in Ireland: potential health effects interfering with performance - Logue, D. M.; Madigan, S. M.; Melin, A.; Mc Donnell, S.-J.; Delahunt, E.; Heinen, M.; Corish, C. A. (European Journal of Sport Science, 2021)
Introduction: The syndrome of Relative Energy Deficiency in Sport (RED-S) consensus statements recognise that male athletes might have impaired fertility in terms of the Exercise Hypogonodal Male Condition (ExHMC). Thus, the aims of this study were to 1) identify risk of ExHMC in active males in various sports and 2) determine if associations between risk of ExHMC and health problems interfering with training and competition exist. Methods: A questionnaire was distributed online (November 2018-January 2019) using questions derived from the `Androgen Deficiency in the Aging Male Questionnaire` (ADAM-Q) to assess risk of ExHMC. Additional questions were included to collect information on participant demographics, injury and illness history and dietary habits. Logistic regression analyses explored differences between groups. Results: Risk of ExHMC was identified in 23.3% (n=185) of 794 questionnaire participants. Following multivariate analyses, risk of ExHMC was independently associated with a lower than normal sex drive rating within the last month (OR 7.62, 95%CI 4.99-11.63) and less than three morning erections per week within the last month (OR: 4.67, 95%CI 3.23-6.76). Risk of ExHMC was associated with 15-21 days absence from training or competition during the previous 6 months due to overload injuries in the univariate analysis (OR = 2.69, 95% CI = 1.24-5.84). Conclusion: Risk of ExHMC and associated symptoms in this heterogeneous sample may be indicative of RED-S. Confounding factors such as over-training, medication use, fatigue and psychological stress need to be considered. Identification of male athletes exhibiting physiological symptoms associated with RED-S requires more research.